Reza Afandy Ghulam1 Fitri² - Ghulam, Reza Afandy Ghulam; Fitri (BJRM (Bongaya Journal For Research in Management), 2025)
Following the enactment of Government Regulation No. 35 of 2021 concerning employment, Makassar City experienced significant economic dynamics during the 2021–2024 period. This study analyzes the economic impact of the regulation on entrepreneurs, workers, and Micro, Small, and Medium Enterprises (MSMEs) in Makassar. The study uses a qualitative approach through interviews with local actors and secondary data analysis. The results show that PP 35/2021 provides flexibility for entrepreneurs and manufacturing industries in managing the workforce, which contributes to regional economic recovery with Makassar's Gross Regional Domestic Product (GRDP) growth increasing from 4.47% (2021) to 5.40% (2022). On the other hand, workers face changes in working conditions, including an increase in the use of short-term contracts and outsourcing, which raises concerns about reduced job security. The MSME sector is gradually recovering with the support of local business incubation programs, although it is still affected by the decline in purchasing power at the beginning of the pandemic. This analysis also discusses local policy responses, such as city government initiatives and union actions demanding revisions to regulations. In conclusion, the implementation of PP 35/2021 in Makassar has brought various economic impacts: economic recovery and reduced unemployment on the one hand, but accompanied by challenges to workers' welfare and the sustainability of MSMEs on the other. Collaborative efforts between local stakeholders are needed to maximize economic benefits while protecting workers' rights. Keywords: PP 35/2021, economic impact, Entrepreneurs, Workers, MSMEs